Exploring China's success at the Olympic Games: a competitive advantage approach - Zheng, J.; Chen, S. (European Sport Management Quarterly, 2016)
Research question: Much research has been carried out to analyse factors contributing to China's notable success at the Olympic Games over the past decade. However, research which examines China's deliberate Olympic medal strategy remains relatively uncharted territory. Thus this paper seeks to address this gap and examines how China has become one of the most successful superpowers at the Summer Olympic Games within the last two decades by virtue of the application of the competitive advantage framework. Research methods: Seven semi-structured interviews were conducted with key stakeholders of elite sport in China. These data were supplemented by a range of official publications of sports governing bodies in China, their websites and related information from the websites of influential media. Results and findings: It is evidenced that China's current Olympic configuration and (gold) medal distribution among sports/disciplines are largely underpinned by Tian Maijiu's research on cluster-based sports training and the `Five-Word principle` (i.e. Small, Fast, Women, Water and Agile). In addition, there is clear evidence of China's continuous expansion of its market and the ambition to greater success in gold-medal abundant and collective ball sports/disciplines. Implications: This article concludes by critically examining the key characteristics and outcomes of China's approach to clustering and prioritisation, attempting to provide some insights into the establishment or refinement of Olympic (gold) medal strategy for other nations, where China may provide some useful lessons. The compatibility of the competitive advantage framework with the analysis of China's Olympic success is also discussed.